Legal Studies Concerning Children As Victims Of Prostitution - Atikah Rahmi (International Journal Reglement & Society (IJRS), 2022)
Prostitution is a sexual crime based on unnatural and uncontrolled sex drive in the form of uncontrolled lust for many people accompanied by exploitation and commercialization. Not a few children who later became victims. This paper discusses the legal study of children as victims of prostitution including the causes and legal protection factors. The research method used in this study is normative legal research using secondary data which is analyzed through content analysis with a statutory approach (statua approach). Based on the research results, it is known that there are many factors behind children becoming victims of prostitution including family, religious and economic factors. Children who are victims of prostitution are given legal protection based on Law Number 23 of 2022 concerning Child Protection.